Evaluation of a monoclonal antibody test to detect chlamydia in cervical and urethral specimens. - Forbes, B A (1986)
The MicroTrak Chlamydia trachomatis Direct Specimen Test (MT; Syva Co., Palo Alto, Calif.) was compared with cell culture in two patient populations. The sensitivity of the MT for a low-prevalence group was significantly lower (59.6%) than that for a high-prevalence group (84.4%). The results underscored the need to run the MT in parallel with culture initially if the prevalence of chlamydial infections is unknown and questioned the usefulness of the MT as a screening test for chlamydia in low-prevalence populations.